2022
DOI: 10.3390/jcm11020415
|View full text |Cite
|
Sign up to set email alerts
|

A Narrative Review of the Association between Post-Traumatic Stress Disorder and Obstructive Sleep Apnea

Abstract: Obstructive sleep apnea (OSA) and post-traumatic stress disorder (PTSD) are often co-morbid with implications for disease severity and treatment outcomes. OSA prevalence is higher in PTSD sufferers than in the general population, with a likely bidirectional effect of the two illnesses. There is substantial evidence to support the role that disturbed sleep may play in the pathophysiology of PTSD. Sleep disturbance associated with OSA may interfere with normal rapid eye movement (REM) functioning and thus worsen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 100 publications
(125 reference statements)
0
6
0
Order By: Relevance
“…In this study, no causal link was found between psychiatric conditions like SCZ, BIP, PTSD, and OSA, diverging from previous research outcomes. Earlier observational studies suggested an increased OSA risk among SCZ patients compared to those without SCZ ( 56 , 57 ) and a higher OSA prevalence in individuals with PTSD and BIP than in the general population ( 10 12 ). However, these contrasts with our MR analysis might stem from confounding elements in observational studies.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In this study, no causal link was found between psychiatric conditions like SCZ, BIP, PTSD, and OSA, diverging from previous research outcomes. Earlier observational studies suggested an increased OSA risk among SCZ patients compared to those without SCZ ( 56 , 57 ) and a higher OSA prevalence in individuals with PTSD and BIP than in the general population ( 10 12 ). However, these contrasts with our MR analysis might stem from confounding elements in observational studies.…”
Section: Discussionmentioning
confidence: 95%
“…The potential link between PDs and OSA has recently garnered increasing research interest ( 5 7 ). Numerous studies indicate a high prevalence of OSA in patients with psychiatric conditions ( 5 , 8 , 9 ), with elevated rates of OSA observed explicitly in patients with post-traumatic stress disorder (PTSD) and bipolar disorder (BIP) compared to the general population ( 10 12 ). Conversely, increased incidences of PDs are reported in individuals with OSA ( 13 , 14 ), with depression and anxiety disorder (ANX) being more common in OSA patients than in non-OSA counterparts ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our participants varied in their history of sleep‐disordered breathing. Participants with a history of obstructive sleep apnea (OSA) were not excluded from the study, due to high levels of comorbidity between PTSD and OSA (Jaoude et al, 2015); however, there is a complex relationship between PTSD and OSA (McCall & Watson, 2022), as well as between surgically implanted VNS and OSA (Dye et al, 2021; Guo et al, 2021; Gurung et al, 2020). Continued research is needed to clarify the relationship between tVNS and OSA and how this may affect application of tVNS to a PTSD population.…”
Section: Discussionmentioning
confidence: 99%
“…A low ArTH is more common in individuals with REM-dependent OSA [ 44 ], and among those who are non-obese, older, and taking antidepressants [ 45 ]. Individuals with post-traumatic stress disorder may also have a lower ArTH, presumably due to their hyperadrenergic state [ 46 ].…”
Section: Osa Traitsmentioning
confidence: 99%